Controlling the efficiency of excision repair - Hanawalt, Philip C. (Mutation research, 2001)
The early studies are recounted, that led to the discovery of the ubiquitous process of DNA excision repair, followed by a review of the pathways of transcription-coupled repair (TCR) and global genomic nucleotide excision repair (GGR). Repair replication of damaged DNA in UV-irradiated bacteria was discovered through the use of 5-bromouracil to density-label newly synthesized DNA. This assay was then used in human cells to validate the phenomenon of unscheduled DNA synthesis as a measure of excision repair and to elucidate the first example of a DNA repair disorder, xeroderma pigmentosum. Features of the TCR pathway (that is defective in Cockayne syndrome (CS)) include the possibility of “gratuitous TCR” at transcription pause sites in undamaged DNA. The GGR pathway is shown to be controlled through the SOS stress response in E. coli and through the activated product of the p53 tumor suppressor gene in human cells. These regulatory systems particularly affect the efficiency of repair of the predominant UV-induced photoproduct, the cyclobutane pyrimidine dimer, as well as that of chemical carcinogen adducts, such as benzo(a)pyrene diol-epoxide. Rodent cells (typically lacking the p53-controlled GGR pathway) and tumor virus infected human cells (in which p53 function is abrogated) are unable to carry out efficient GGR of some lesions. Therefore, caution should be exercised in the interpretation of results from such systems for risk assessment in genetic toxicology. Many problems in excision repair remain to be solved, including the mechanism of scanning the DNA for lesions and the subcellular localization of the repair factories. Also there are persisting questions regarding the multiple options of repair, recombination, and translesion synthesis when replication forks encounter lesions in the template DNA. That is where the field of DNA excision repair began four decades ago with studies on the recovery of DNA synthesis in UV-irradiated bacteria.